Alveolar Biomarker Profiles in Subphenotypes of the Acute Respiratory Distress Syndrome. Issue 1 (8th November 2022) - Sathe, Neha A.; Morrell, Eric D.; Bhatraju, Pavan K.; Fessler, Michael B.; Stapleton, Renee D.; Wurfel, Mark M.; Mikacenic, Carmen
Abstract : OBJECTIVES: We sought to determine whether hyperinflammatory acute respiratory distress syndrome (ARDS) and hypoinflammatory ARDS, which have been associated with differences in plasma biomarkers and mortality risk, also display differences in bronchoalveolar lavage (BALF) biomarker profiles. We then described the relationship between hyperinflammatory ARDS and hypoinflammatory ARDS to novel subphenotypes derived using BALF biomarkers. DESIGN: Secondary analysis of a randomized control trial testing omega-3 fatty acids for the treatment of ARDS. SETTING: Five North American intensive care units. PATIENTS: Adults ( n = 88) on invasive mechanical ventilation within 48 hours of ARDS onset. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We classified 57 patients as hypoinflammatory and 31 patients as hyperinflammatory using a previously validated logistic regression model. Of 14 BALF biomarkers analyzed, interleukin-6 and granulocyte colony stimulating factor were higher among patients with hyperinflammatory ARDS compared with hypoinflammatory ARDS, though the differences were not robust to multiple hypothesis testing. We then performed a de novo latent class analysis of the 14 BALF biomarkers to identify two classes well separated by alveolar profiles. Class 2 ( n = 63) displayed significantly higher interleukin-6, von Willebrand factor, soluble programmed cell death receptor-1, % neutrophils, and other biomarkers of inflammation compared with class 1 ( n = 25). These BALF-derived classes had minimal overlap with the plasma-derived hyperinflammatory and hypoinflammatory classes, and the majority of both plasma-derived classes were in BALF-derived class 2 and characterized by high BALF biomarkers. Additionally, the BALF-derived classes were associated with clinical severity of pulmonary disease, with class 2 exhibiting lower Pao 2 to Fio 2 and distinct ventilatory parameters, unlike the plasma-derived classes, which were only related to nonpulmonary organ dysfunction. CONCLUSIONS: Hyperinflammatory and hypoinflammatory ARDS subphenotypes did not display significant differences in alveolar biologic profiles. Identifying ARDS subgroups using BALF measurements is a unique approach that complements information obtained from plasma, with potential to inform enrichment strategies in trials of lung-targeted therapies.